Optical soliton perturbation with quadratic-cubic nonlinearity by Adomian decomposition method - Asma, Mir; Othman, Wan Ainun Mior; Wong, Bernardine Renaldo; Biswas, Anjan (Elsevier, 2018)
This paper studies optical soliton perturbation that appears with quadratic-cubic nonlinearity, by the aid of Adomian decomposition method (ADM). Bright, dark and W-shaped solitons are examined that are obtained by the aid of this numerical scheme. The error plots are also given to give a taste of the accuracy of this scheme.